Comparison of Outcomes in Medical Therapy vs Surgical Intervention of Esophageal Foreign Bodies. (October 2018) - Lin, Austin Y.; Tillman, Brittny N.; Thatcher, Aaron L.; Graves, Casey R.; Prince, Mark E.
Objectives: (1) Compare efficacy of primary medical therapy vs primary surgical intervention in patients with esophageal foreign bodies (EFBs). (2) Investigate variables that may predict successful outcomes in patients treated for EFBs. Study Design: Case series with chart review. Setting: Single-institution academic tertiary care medical center. Subjects and Methods: Adult patients (older than 18 years) seen at the University of Michigan Emergency Department (ED) over an 8-year period with the diagnosis of EFBs (January 1, 2003, to December 31, 2011; N = 250). Decision was made by ED physicians whether to treat patients with first-line medical therapy vs surgical intervention. Pertinent clinical and demographic data were extracted from medical records and summarized by descriptive statistics. Results: First-line treatment with surgical intervention (flexible or rigid esophagoscopy with foreign body removal) was much more likely to lead to resolution of symptoms than medical therapy (glucagon alone or in combination with other medical therapy) (98% vs 28%, P < .0001). When delivered within 12 hours of symptom onset, medical therapy was more likely to be successful (34% resolution vs 12% resolution, P < .01). There was no difference in complication rates for primary medical therapy vs surgical intervention (8% vs 8%). Conclusions: Patients with EFBs are a commonly encountered consultation for both otolaryngologists and gastroenterologists. In these patients, first-line surgical intervention is superior to medical therapy and should not be avoided for a trial of medical therapy or concern for higher morbidity. Implementation of these findings has the ability to positively affect treatment patterns, outcomes, and patient quality of life.